Eficacia del digital storytelling como estrategia didáctica en el desarrollo de competencias digitales en estudiantes de educación - Sulca Quispe, Rafael (2022)
The research evaluated the effectiveness of digital storytelling (DST) in the development of digital skills in its different areas, in university students of a public entity. The approach was quantitative, quasi-experimental. The sample was non-random, of 62 participants distributed in a control and experimental group. A Digital Competence Questionnaire was initially administered to both groups in their different areas. The students of the experimental group elaborated a weekly digital storytelling for 3 months within the framework of their study subjects, while the control group did not. Subsequently, both groups were administered the post-test of the different areas of digital skills. The results showed a significant increase in the general quotient of digital skills and in the areas of digital skills of problem solving, security, content development, communication and information. It remains as a suggestion to intensify the use of DST to increase digital skills.